An Evaluation Tool for Story-Relatedinteractive Features in Children App-Book - Dianing Ratri; Yoomi Choi (KK Komunikasi Visual & Multimedia Fakultas Seni Rupa dan Desain Institut Teknologi Bandung, 2014)
This study discusses existing analysis tools that evaluate the quality of interactive feature inside children app-book especially its correlation with the story in order to find a better app-book design to support story comprehension for young children. To implement the evaluation, a narrative review approach is used from selected studies and field. Five analysis tools related to e-book design were reviewed based on their purpose, coding, advantages and limitation. For knowledge base, the study seeks across interactive design field along with children literature and children education field to presents what it needs to produce coding for story-related interactive feature. The combination between existing analysis tool and literature studies are extracted into coding of story-related interactive feature. Finally, the result presents an evaluation tool with coding which can define the correlation function between interactive features in story inside children app-book, which also can improve users' story comprehension.